Cideb Deficiency Aggravates Dextran Sulfate Sodium-induced Ulcerative Colitis in Mice by Exacerbating the Oxidative Burden in Colonic Mucosa. Issue 8 (August 2017) - Sun, Chao; Zhao, Yuanlin; Gao, Xing; Yuan, Yuan; Wang, Chao; Wang, Yingmei; Zhang, Lijun; Gu, Yu; Zhang, Feng; Hu, Peizhen; Wang, Zhe; Li, Zhuyi; et al.
Abstract : Background: Abnormal lipid metabolism is one of many factors that contribute to the development of ulcerative colitis (UC). As a lipid droplet–associated protein, Cideb facilitated the export of lipids from enterocytes and promoted intestinal lipid absorption. We found that Cideb was upregulated in the colonic mucosa of both UC patients and dextran sodium sulfate (DSS)-induced mouse colitis, but its roles in the pathogenesis of UC are still ill-defined. Methods: Acute colitis was induced with DSS in Cideb -null and wild-type mice, and the inflammation and oxidative stress were evaluated in the colonic mucosa. Moreover, triglyceride accumulation and oxidative stress were further analyzed in polarized Caco-2 cells with overexpression of Cideb. Results: Our present data indicated that Cideb -null mice were more susceptible to DSS-induced colitis, and consumption of a high-fat diet exacerbated the deterioration of DSS-induced colitis in Cideb -null mice. Moreover, Cideb deficiency increased the colonic oxidative stress in DSS-treated mice and more significant under a high-fat diet condition. In exploring the mechanism, we found that Cideb deficiency elevated the lipid content in both feces and the colonic mucosa of DSS-treated mice, especially those fed with a high-fat diet. The in vitro evidence proved that Cideb expression reduced triglyceride accumulation and oxidative stress in polarized Caco-2 cells in the presence of oleic acid. Conclusions: Our data suggest that Cideb plays a protective role against the development of UC by reducing the lipid accumulation and oxidative damage in the colonic mucosa. Therefore, Cideb could be a potential therapeutic target for UC. Abstract : Article first published online 17 July 2017.Supplemental Digital Content is Available in the Text.